Kuntze Metabolite Profile and Antioxidant Activity of Vincetoxicum villosum (Blume) Kuntze - Sari, Anjeli Rama; Ruyani, Aceng; Ismaini, Lily; Hartuti, Endah Dwi (Departemen Kimia, 2025)
Vincetoxicum villosum belongs to the Apocynaceae family. V. villosum is often used as a traditional medicine for treating jaundice, gallstones, kidney stones, hepatitis B, and liver diseases. This study aims to determine the metabolite profile and antioxidant activity of V. villosum to provide new information and serve as a reference for its safe use as a medicinal plant. The methods used to determine the metabolite profile involved GC-MS, and antioxidant activity was assessed using the DPPH method. GC-MS analysis showed that V. villosum leaf extract contains n-hexadecanoic acid, phytol, 9,12,15-octadecatrienoic acid (Z,Z,Z)-, and 2,4-di-tert-butylphenol which have potential antioxidant activity. The antioxidant activity in V. villosum leaves is classified as very weak, with IC50 ranging 0.6 – 1.6 mg/mL, with the best antioxidant activity observed in polar solvents (ethanol extract) with a maceration time of 72 hours. The highest total phenol content was obtained using ethanol solvent with a maceration time of 72 hours, amounting to 416.17 mg GAE/g, and the highest total flavonoid content was obtained using ethyl acetate solvent with a maceration time of 24 hours, amounting to 168.78 mg QE/g